Contribution of the solar systems to the nZEB and ZEB design concept in Portugal: energy, economics and environmental life-cycle analysis - Silva, Sandra Monteiro (2016)
The recast of the Energy Performance of Buildings Directive settle that by 2020 all new buildings should reach nearly zero energy levels (2018 for buildings owned or occupied by public authorities). Therefore, technicians involved in the design, management and approval of buildings should be able to understand and apply nearly zero energy buildings (nZEB) concepts in both new buildings and refurbishment of existing ones. At European Union (EU) level there are differences in commitment to the EU targets and the construction of nZEB. Therefore, it is necessary to develop studies that demonstrate the advantages of the nZEB and ZEB design process that can increase the awareness of both building clients and other stakeholders regarding this issue. In this context, the aim of this paper is to assess the energy and environmental life-cycle performance of different renovation scenarios (Basic Renovation, nZEB and ZEB) for multifamily buildings in Portugal. This will be focused on the goals of the nZEB and ZEB design process and on the contribution of solar systems (both solar thermal collectors, STCs, and photovoltaic panels, PVs) to the achievement of those goals. The results presented in this paper show that, in the Portuguese climate and for a typical multi-family building, it is possible to overcome 100% of the energy needs for acclimatization and domestic hot water (DHW) preparation with the integration of solar systems. From the results, it is also possible to conclude that a significant amount of energy and carbon emissions are avoided for every renovation scenario during the considered lifetime (30 years) and that the nZEB and ZEB scenarios are cost-effective with attractive payback times.